MENUMBUHKAN SIKAP SELF-CONFIDENT DENGAN TEMA PUISI PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV MI AL-IKHWAN - Junita Karinah; Salman; Sakban; Yesika Novita Rahmi (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
Each individual and student has a unique environment and background. This environment influences the development of character and self-confidence. However, many children in Indonesia still experience a lack of self-confidence. In fact, Indonesian children experience a crisis of confidence, despite possessing extraordinary talents. A child's lack of self-confidence will impact their learning process and adaptation to their new environment. Observations indicate that many students at MI Al-Ikhwan Tandun still have low self-confidence. The purpose of this study was to determine the group's efforts to increase children's self-confidence, to identify factors contributing to low and high self-confidence, and to identify teachers' challenges in fostering self-confidence. This study is a qualitative field research study. Data collection methods used were observation, interviews, and documentation. The results identified various efforts made by teachers, including providing motivation and appreciation to students. However, teachers also face challenges such as unstable student moods and limited infrastructure. And there are several factors that influence the level of self-confidence in children.